Hepatitis B Prevalence in Upper Dolpo in the Mid Western Development Region/Nepal - Menner, A S; Dixit, S; Kinkel H T; Küpper, T (2016)
Background: Hepatitis B is one of the most common viral infections in the world. Almost one third of the World´s population has been infected with the virus and about 350 Million people live with chronic infection resulting in up to 30% of affected people to liver fibrosis, cirrhosis and hepatocellular carcinoma. Especially in low resource countries hepatitis B is highly endemic with predominant vertical transmission, mostly leading to chronicity. In Upper Dolpo, a remote and former Tibetan part of Dolpo District in the Nepalese Himalaya, modern health care services are virtually absent. Many Dolpo move to Kathmandu during winter to seek health care in the free of charge “winter clinic”. Methods: In Jan/Feb 2014, HBV, HDV and HIV-serology as well as risk factors of transmission and alcohol consumption patterns were assessed among all Dolpo attending the winter clinic. Results: 65 of 304 patients (21.4%) were tested positive for HBs-AG. 13% of the women in childbearing age were found to be HBe-antigen positive Hepatitis B carriers with a very high risk of vertical transmission to the child. Of 50 children ≤ 12 years, 12 (22%) have been infected with HBV, 9 (75%) of them chronically. In a logistic regression model the odds of acquiring HBV was significantly increasing by 1.53% (95%CI: 0.23-2.8%) per life year (life-time risk) and we could proof a significant inverse correlation between age and chronicity of 2% per life year (95% CI: 0-4%). No HDV co-infection was found and all patients were tested negative for HIV. 50% of the patients, surveyed in the AUDIT have risky patterns of alcohol consumption (AUDIT score >8) and 18% were found with an AUDIT score >20, which is highly suggestive to hazardous alcohol use disorder. The results of the questionnaire on hepatitis B risk behavior indicated a high potential of acquiring sexually transmitted diseases. Conclusions: The high endemicity of chronic HBV infections is in line with findings in Tibet and is in contrast to the generally low endemicity in other parts of Nepal. The overwhelming majority of the chronic infections is acquired prenatally or in early infancy. Implementation of newborn HBV-vaccination programs must therefore have highest priority. More detailed investigations as well as awareness and education campaigns regarding liver health, alcohol use disorder and viral hepatitis are of utmost importance. Keywords: Hepatitis B; prevalence; risk factors; winter clinic.